2021
DOI: 10.1093/jpe/rtab002
|View full text |Cite
|
Sign up to set email alerts
|

In nomen omen: the effect of flower distance on female reproductive success of the lax-flowered orchidAnacamptis laxiflora(Orchidaceae)

Abstract: Aims In multiflowered species, the architecture of inflorescences is of primary importance in shaping plant attractiveness. The aim of this study was to disentangle the role of inflorescence traits in plant female reproductive success and pollination patterns along the inflorescence in the lax-flowered orchid Anacamptis laxiflora, a terrestrial species exploiting a deceptive pollination strategy. We also evaluated whether the relationship between inflorescence traits and female reproductive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The effects of inflorescence display on reproductive success is often found to be under pollinator‐mediated selection (Trunschke et al, 2017). In the deceptive orchids Cypripedium acaule , Dactylorhiza lapponica and Anacamptis laxiflora the strength of pollinator‐mediated selection on an inflorescence depended on the surrounding vegetation (O'Connell & Johnston, 1998; Sletvold et al, 2010; Scopece et al., 2021). Inflorescence traits and visual display size traits are known to be important for long‐distance attraction of pollinators (Boff et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of inflorescence display on reproductive success is often found to be under pollinator‐mediated selection (Trunschke et al, 2017). In the deceptive orchids Cypripedium acaule , Dactylorhiza lapponica and Anacamptis laxiflora the strength of pollinator‐mediated selection on an inflorescence depended on the surrounding vegetation (O'Connell & Johnston, 1998; Sletvold et al, 2010; Scopece et al., 2021). Inflorescence traits and visual display size traits are known to be important for long‐distance attraction of pollinators (Boff et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of flower position on natural capsule production has been studied in a variety of deceptive orchid species, and heterogeneity of results in these patterns have been observed. The probability of capsule formation in orchids has often been found to be related to flower position within an inflorescence, related to competition among developing fruits for resources, differential floral attraction of pollinators, quantity and/or quality of pollen received, and surrounding vegetation (Brundrett, 2019; Baguette et al, 2020; Scopece et al., 2021). In plants whose flowers open sequentially, pollen from flowers at different positions may have different opportunities to sire offspring (Brunet & Charlesworth, 1995; Vallius, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The studies of relationships between the morphological and/or phenological traits and female and male success in food-deceptive orchids are well-documented (Mattila & Kuitunen, 2000;Sletvold & Ågren, 2014;Sletvold et al, 2010;Trunschke et al, 2017;Vallius et al, 2007). However, these studies encompass only single-year data sets and reveal associations such as the impact of floral display on fruit set in Anacamptis longicornu (Capó et al, 2019), the density of co-flowering rewarding plants in Orchis militaris (Henneresse et al, 2017), floral display in Caladenia valida and Tolumnia variegata (Tremblay et al, 2010), inflorescence traits in the environmental context in Anacamptis laxiflora (Scopece et al, 2021), as well as flower brightness (Sletvold et al, 2016), flower color (Trunschke et al, 2021), and flowering time (Sabat & Ackerman, 1996). The long-term study showed only Scopece et al (2017), who revealed weak directional selection in nine morphological traits in Orchis mascula and O. pauciflora.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, we need further evidence to support the argument. Previous studies have shown that differences in primary and physiological traits between the sexes strongly depend on the plant species and their environmental conditions, and that they may arise from a number of reasons, such as differences in trait optima of each sex along a series of resource gradients, sexual selection and sex-specific responses to sexual selection (Barrett and Josh 2013;Geber et al 1999;Juvany and Munné-Bosch 2016;Kohorn et al 1994;Rabska et al 2021;Retuerto et al 2018;Scopece et al 2021;Wang et al 2021).…”
mentioning
confidence: 99%